2017
DOI: 10.22266/ijies2017.1231.24
|View full text |Cite
|
Sign up to set email alerts
|

Image Encryption Method based on Hybrid Fractal-Chaos Algorithm

Abstract: Abstract:In recent years, there has been an increasing interest in the field of cryptography. Cryptography has applied in diverse applications and the researchers mainly concentrates on Image Encryption (IE) field. This paper proposes a hybrid encryption technique in order to provide high secure transmission. Here, an IE and decryption process is proposed by employing hybrid fractal-chaos technique. This proposed methodology consists of four modules like key generation, fractal encryption, chaos encryption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…of the methods in this article, it can be observed that the two methods can both be used to evaluate the continuity level of the detection results of different image features, but the method put forward in this paper can distinguish the images more effectively. In addition, the evaluation time of the method put forward in this paper is less than that of the method described in literature [11][12][13][14]. Hence, it has significant advantages in the application.…”
Section: Settings Of the Main Parametersmentioning
confidence: 96%
“…of the methods in this article, it can be observed that the two methods can both be used to evaluate the continuity level of the detection results of different image features, but the method put forward in this paper can distinguish the images more effectively. In addition, the evaluation time of the method put forward in this paper is less than that of the method described in literature [11][12][13][14]. Hence, it has significant advantages in the application.…”
Section: Settings Of the Main Parametersmentioning
confidence: 96%
“…UACI and NPCR are used to measure the encryption strength of sensitivity and differential attacks [19,[30][31]. Where the formula used to calculate UACI and NPCR is shown in formulas (13) and (14).…”
Section: Resultsmentioning
confidence: 99%
“…Image is one of the medias that has been widely used as a medium for cryptography implementation, where the scramble, stream, and substitution methods have been tested. The scramble method is also often called the permutation or diffusion method [10] where, algorithms that are widely in this method are Chaotic Map [5,[11][12][13]. Whereas the algorithms that are popular used in substitution methods are one-time pad (OTP), Vigenere, Hill cipher, etc [1,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Event-B can be regarded as a method for correct-by-construction software development. Event-B has gained widespread attention with it tool support which can be employed to specify different communication protocols as in [11], wireless communication [12], Wireless Sensor Networks [13] or in hybrid encryption technique [14].…”
Section: Introductionmentioning
confidence: 99%